Molecular characterization of immunoglobulin D in mammals: immunoglobulin heavy constant delta genes in dogs, chimpanzees and four old world monkey species - Rogers, Kenneth A (Blackwell Science Inc, 2006)
Antibodies are adaptor molecules that neutralize pathogens and link humoral and cellular defence mechanisms. Immunoglobulin D (IgD), one of the five antibody classes present in mammals, is expressed as an antigen receptor on naïve B cells. The functional role that IgD plays in the immune response is still poorly understood, but the recent characterization of immunoglobulin heavy constant delta genes (IGHD) in a variety of species challenges the view that IgD is of minor importance and is not present in many animals. On the basis of serological studies, IgD appears to be expressed in the majority of mammalian species examined. To confirm, at the molecular level, that IgD is present in different species, we cloned and sequenced IGHD cDNA from dogs and five non-human primate species (chimpanzee, rhesus macaque, cynomolgus macaque, baboon and sooty mangabey). Our results show that in all six species, IgD heavy chains possess three immunoglobulin domains and a long hinge region encoded by two exons. Only the hinge region of non-human primates is similar to the human hinge region, with conservation of O-glycosylation sites and multiple charged residues at opposing ends. The preservation of IgD in primates, dogs and previously characterized species suggests an important functional role for IgD, possibly involving binding to a receptor. The high degree of similarity existing between the structural features of human and non-human primate IgD suggests that non-human primates are suitable for in vivo studies designed to define the role that IgD plays in the immune response.